CLASSIFICATION OF PULMONARY METASTASES: POTENTIAL APPLICATION IN CLINICAL PRACTICE - E. I. Smolenov; Yu. A. Ragulin; O. V. Pikin (Сибирский онкологический журнал)
Background. There is currently no information on the results of randomized studies evaluating the surgical treatment outcomes in patients with pulmonary metastases. Therefore, there is a strong need for a staging system that can permit the stratification of patients with intrapulmonary metastasis. Aim: To analyze the overall survival of patients who underwent pulmonary metastasectomy using a new classification taking account the extent of pulmonary metastasis. Material and methods. The study included 568 lung cancer patients who underwent pulmonary metastasectomy. All patients were stratified according to a new classification taking into account the number of metastatic sites and the extent of lymph node involvement. The median age of the patients was 49 years (range: 18 to 81 years). Results. Histological study revealed no evidence of metastases in 72 patients. In patients having no lymph node involvement, better results were observed in patients with a solitary site of metastasis (Ms ), with a median survival of 58 months. In patients with oligometastatic lesions (up to 5 sites) and limited metastatic sites (6–24 sites), the median survival was 36 and 26 months, respectively. In patients with multiple metastatic lesions (more than 25 sites), the median survival was 12 months. Among patients with lymph node metastases, the median survival was 32 months for patients with a solitary metastasis (Ms) and 27 months for patients with oligometastases (Mo ). In patients with limited number of metastatic sites (6–24 sites), the median survival was 12 months. In patients with multiple metastases (Mm), the median survival was 6 months (p=0.00012). Conclusion. A new classification will help to stratify patients into identical subgroups. Its use should be considered as one of the selection criteria in future multicentre randomized trials.